Enhancing Customer Satisfaction Through AI Chatbots and Electronic Service Quality - Suci Adella Fatmawati; Siska Ernawati Fatimah (International Journal Labs, 2026)
The growth of the e-commerce platform has stimulated the utilisation of the digital-based technology as the means of enhancing the service and customer satisfaction. It seeks to explore the relationship between the quality of e-services and AI chatbots to determine customer satisfaction in e-commerce websites Cirebon City. This is a quantitative study in which 200 representatives aged 15-40 years were used to gather data by using a structured questionnaire. Structural Equation Modeling Partial Least Squares (SmartPLS) is employed as the technique of data analysis. The outcome is that the electronic service quality will be more influential with the coefficient of 0.553, and AI chatbots will have a positive influence with the path coefficient of 0.296. The R² obtained is 0.613, which is a result that the quality of AI chatbots and electronic services can explain 61.3 percent of the changes in the customer satisfaction. These results demonstrate that the electronic service quality is the dominant factor when it wants to raising the level of customer satisfaction and that chatbots based on artificial intelligence can improve the user experience provided in case of the interaction with the e-commerce websites.